Genetic analysis of HIV-1 integrase sequences from treatment naive individuals in Northeastern South Africa - Bessong, Pascal Obong; Nwobegahay, Julius (Molecular Diversity Preservation International (MDPI), 2013)
Raltegravir, an integrase inhibitor, is not a component of the current South African antiretroviral treatment guidelines, but it could be introduced in the near future as cases of virological failures from current treatment regimens begin to occur. The aim of this study was to analyze the complete HIV integrase gene obtained from individuals at two treatment sites in northeastern South Africa for the presence of Raltegravir associated drug resistant mutations and viral subtypes based on the integrase gene. Examination for mutations against other integrase inhibitors, such as Elvitegravir and Dolutegravir, was also done. Viruses from 127 treatment naive individuals were analyzed. Genetic drug resistance mutations were determined using the Stanford HIV Drug Resistance Interpretation program and the International AIDS society-USA guidelines. Viral subtyping was done by phylogenetic analysis, and recombinants were determined using the REGA, jpHMM and RIP tools. No major resistance mutations were detected. However, 7% of the sequences had minor mutations and polymorphisms. The majority (99%) of the viruses were HIV-1 C. Recombination analysis showed that the polymerase gene of one virus was likely composed of HIV-1 subtype A1 and C sequences. The present study indicates that Raltegravir, Elvitegravir and Dolutegravir resistant mutations may be absent in the study communities and further indicates the presence of recombinant viruses in northeastern South Africa.
Publication of this article was funded by HIV/AIDS & Global Health Research Programme, University of Venda, Department of Microbiology
Keywords: HIV-1 integrase; UCTD; raltegravir genetic resistance; polymorphisms; viral recombinants; northeastern South Africa